SPECIAL PROPERTIES OF THE LEFT VENTRICLE MYOCARDUM REMODELING IN ATHLETES WITH ARTERIAL HYPERTENSION - N. V. Fomina; O. A. Ronzhina; S. A. Smakotina (Российский кардиологический журнал, 2015)
Aim. To assess the specifics of myocardium remodeling in sportsmen-weightlifters according to presence of arterial hypertension (AH).Material and methods. Totally 80 sportsmen-weightlifters were included at the age of 21,0 (18,5-25,0) years. Group of AH consisted of 42 (52,5%) men, and the group without AH — 38(47,5%). Investigation consisted in office BP measurement, ambulatory BP monitoring (ABPM), echocardiography (EchoCG). Results. In the group with AH index of left ventricle myocardial mass (ILVMM), left atrium sizes (LA), end-diastolic size (EDS), thickness of interventricle septum (IVS) and posterior wall of the left ventricle (PWLV) were significantly higher than in the group with normal BP. Left ventricle hypertrophy (LVH) (ILVMM >115 g/m2) was found in 8 (19,0%) of athletes with AH and in 5 (13,1 %) — without AH. By the results of regression and correlational analysis it was found that thickness of the left ventricle wall, ILVMM, LA size are closely related to mean values of SBP and DBP during the 24-hour period, including daytime and nocturnal values and pulse wave value. In weightlifters with AH we found statistically significant positive link of LA size and pulse pressure (r=0,47; p=0,0001). Diastolic dysfunction of the left ventricle(DDLV) was found in 12 (15%) of athletes, all of them had AH. Among sportsmen with the signs of DDLV normal geometrical properties of LV were found in 5 (41,6%), concentric remodeling in 1 (8,3%), concentric hypertrophy in 3 (25%) and eccentric hypertrophy in 3 (25%) of weightlifters.Conclusion. Pathological types of LV remodeling (concentric and eccentric hypertrophy) are significantly more prevalent in sportsmen with AH. AH predefines development of DDLV in weightlifters. In sportsmen without AH there is no diastolic dysfunction either with or without LVH.